A note on exact solution for thermal radiative flow over a stretching/shrinking sheet with convective boundary condition - Khan, Masood; Rahman, Masood Ur; Mohammad, Azram (Walailak University, 2016)
An analytical study of thermal radiation in the boundary layer flow through porous medium of an electrically conducting incompressible fluid over a stretching/shrinking sheet in the presence of convective boundary condition is presented. The flow is permeated by an externally applied magnetic field normal to the plane of flow. The equations governing the flow and heat transfer are reduced into a set of nonlinear ordinary differential equations and exact solutions are obtained. The effects of various parameters entering into the problem on the velocity and temperature distribution are discussed and depicted graphically. This study reveals that convective boundary condition results in temperature slip at the sheet and this temperature slip is significantly influenced by the Biot number. © 2016 Walailak University. All rights reserved.